Preparation of a TiO2 nano photocatalyst, doped with silver on a stainless-steel substrate (Ag-TiO2/SS304), and applying it for degradation of the Acid dye (Red131) using photo electrocatalytic technology. (Damascus University Journal for the basic sciences, 2026)
Research efforts aimed to find an effective technology for degradation of pollutants from water, the most important one is photo electrocatalytic (PEC)technique, which is considered as a promising technology for removing a wide range of pollutants (organic, inorganic, biological), and also plays an effective role in reducing the concentration of CO2 gas, in producing electricity, and in the generation of hydrogen from the dissociation of water. In this research, we synthesized a nano-photocatalysts of TiO2, as well as nano-photocatalysts doped with silver (Ag-TiO2) with different weight percentages, by using the Sol-Gel method on glass substrate to reduce the value of the energy gap. The prepared photocatalysts were characterized using molecular absorption spectroscopy for UV absorption and reflectance spectra. They were also described morphologically using an atomic force microscope (AFM). The best weight percentage of silver was chosen and characterized by FT-IR.SS304 stainless steel was used as a substrate to stabilize the prepared catalyst for both the undoped (TiO2/SS304) photoanode and the doped photoanode (Ag-TiO2/SS304), due to its abundance and low cost. The photocatalytic efficiency of the photoanode prepared under UV rays was estimated by studying the degradation of the dye (Acid red 131), as it is a typical organic pollutant. The doped anode gave a higher removal rate compared to the undoped anode. In addition, the results of the study showed that the kinetics of the photoelectrocatalytic degradation reaction of the studied dye (Acid red 131) for both the prepared anodes were first-order, where the value of the dye’s rate constant using the doped anode was higher than that of using the undoped anode.
Keywords: Nano photocatalysts; Sol-Gel; Stainless steel (SS304); Doped photocatalyst; Photoelectrocatalysis (PEC).